Risk assessment of osteoradionecrosis associated with periodontitis using 18F-FDG PET/CT. Issue 132 (November 2020) - Ito, Kotaro; Takumi, Koji; Meibom, Sara K.; Qureshi, Muhammad Mustafa; Fujima, Noriyuki; Andreu-Arasa, V. Carlota; Truong, Minh Tam; Salama, Andrew R.; Kaneda, Takashi; Sakai, Osamu
Highlights: 18 F-FDG PET/CT is a useful tool to evaluate the metabolic activity of periodontitis. Periodontal staging III and SUVmax (>2.1) were significantly associated with occurrence of ORN after RT. 18 F-FDG PET/CT can help predict ORN risk associated with periodontal disease in patients with OP/OC SCC receiving RT. Abstract: Purpose: Osteoradionecrosis (ORN) is a serious complication after radiotherapy (RT), even in the era of intensity modulated radiation therapy (IMRT). The purpose of this study was to evaluate whether 18 F-FDG PET/CT can predict ORN associated with periodontal disease in patients with oropharyngeal or oral cavity squamous cell carcinoma (OP/OC SCC) undergoing RT. Methods: One hundred and five OP/OC SCC patients treated with RT who underwent pretreatment 18 F-FDG PET/CT between October 2007 and June 2016 were retrospectively reviewed. A post-treatment diagnosis of ORN was made clinically based on presence of exposed irradiated mandibular bone that failed to heal after a period of three months without persistent or recurrent tumor. The maximum standardized uptake value (SUVmax) of periodontal regions identified on PET/CT was measured for all patients. Image-based staging of periodontitis was also performed using American Academy of Periodontology staging system on CT. Results: Among 105 patients, 14 (13.3 %) developed ORN. The SUVmax of the periodontal region in patients with ORN (3.35 ± 1.23) was significantly higher than patients without ORN (1.92 ± 0.66) ( P  <  .01). The corresponding CT stage of periodontitis in patients with ORN was significantly higher (2.71±0.47) than patients without ORN (1.80±0.73) ( P  <  .01). ROC analysis revealed the cut-off values of developing ORN were 2.1 in SUVmax, and II in CT stage of periodontitis. The corresponding AUC was 0.86 and 0.82, respectively. Conclusions: Pretreatment 18 F-FDG PET/CT identification of periodontitis may be helpful to predict the future development of ORN in patients with OP/OC SCC undergoing RT.